Predictive ability of the health belief model in HIV testing and counselling uptake among youth aged 15-24 in La-Nkwantanang-Madina Municipality, Ghana - Rosemond Appau; Richard Gyan Aboagye; Morkporkpor Nyahe; Nelisiwe Khuzwayo; Elvis Enowbeyang Tarkang (BMC, 2024)
Abstract Background Majority of new Human Immunodeficiency Virus (HIV)-positive persons in Ghana are aged 15-24. HIV prevalence among persons aged 15-24 years, a proxy for new infections, remained stable at 1.5% for 2017 and 2018, making it a significant public health concern. Yet only 26.4% of females and 8.6% of males aged 15-24 years know their HIV status. This study determined the predictive ability of the Health Belief Model (HBM) in HIV testing and counselling (HTC) uptake among youth (15-24 years) in the La-Nkwantanang Madina Municipality, Ghana. Methods A cross-sectional design was adopted for the study, using a multistage sampling method to select 415 youth aged 15-24. Data were collected using a structured interviewer-administered questionnaire, and analysed using binomial logistic regression with STATA software version 16.0 at p < 0.05 significance level and at 95% confidence interval. Results HTC uptake was 29.2%. Perceived susceptibility, perceived barriers, and perceived self-efficacy predicted HTC uptake. Youths with a high-risk perception for contracting HIV [OR = 3.03; 95% CI = 1.46, 6.30, p = 0.003], who perceived that they can contract HIV if not protected [OR = 3.69; 95% CI = 1.47, 9.22, p = 0.005], and worry about getting HIV [OR = 3.03, 95% CI = 1.61, 5.69, p < 0.001] (perceived susceptibility) were more likely to uptake HTC. Youths who had no trust issues with health workers [OR = 3.53; 95% CI = 1.46, 8.53, p = 0.005] and those who were not afraid of positive HIV test results [OR = 5.29; 95% CI = 2.66, 10.51, p,0.001] (perceived barriers) were more likely to uptake HTC. Youths who had no difficulties in turning up for appointments (perceived self-efficacy) had higher odds of HTC uptake [OR = 11.89, 95% CI = 6.73, 20.98, P < 0.001]. For the modifying factors, being married [OR = 2.96; 95% CI = 1.65-5.33], and having knowledge of HTC [OR = 9.10; 95% CI = 2.16-38.3], significantly influenced HTC uptake. Conclusion Health promotion interventions to increase HTC uptake should focus on heightening the perception of susceptibility to HIV, reducing the barriers to HTC uptake, and increasing the self-efficacy for HTC uptake. The interventions should also target the significant modifying factors.